Farming System in Developing Agricultural Business and Efforts to Increase Agricultural Yields in Haturisa Hamlet, Hutumuri Village, South Leitimur District - Iwamony, Grinalda Selfy; Sihasale, Daniel Anthoni; Lasaiba, Mohammad Amin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
Farming System in Developing Agricultural Business and Efforts to Increase Agricultural Yields in Haturisa Hamlet, Negeri Hurutmuri, South Leitimur District; by looking at the process of the farming system that is carried out, everything by the stages and development is also found in agricultural businesses. Farming businesses need efforts to increase agricultural yields. This study aims to determine the farming system and efforts to increase agricultural yields in Haturisa Hamlet, Negeri Hutumuri, South Leitimur District. The type of research used is descriptive quantitative using the SWOT analysis method, with a sample size of 50 farmers. The results of the study showed that farmers in Haturisa Hamlet, Negeri Hutumuri, and South Leitimur District all carried out the farming system correctly; the crops planted by farmers also varied, namely mixed crops, the number of plants usually planted >150, farmers also have efforts to increase agricultural yields in agricultural businesses. In addition, from the results of the data analysis collected using the SWOT analysis method, it can be seen that the position of farm businesses in Haturisa Hamlet, Hutumuri Village, South Leitimur District, is located namely the aggressive approach (Growth Oriental Strategy), this position indicates an opportunity, meaning that in this condition it is possible to continue to expand.